Controlling Interfacial Reduction Kinetics and Suppressing Electrochemical Oscillations in Li4Ti5O12 Thin‐Film Anodes. (6th August 2021) - Chen, Yue; Pan, Handian; Lin, Chun; Li, Jiaxin; Cai, Rongsheng; Haigh, Sarah J.; Zhao, Guiying; Zhang, Jianmin; Lin, Yingbin; Kolosov, Oleg V.; Huang, Zhigao
Abstract: Understanding the fundamentals of surface decoration effects in phase‐separation materials, such as lithium titanate (LTO), is important for optimizing the lithium‐ion battery (LIB) performance. LTO polycrystalline thin‐film electrodes with and without doped Al–ZnO (AZO) surface coating decoration are used as ideal models to gain insights into the mechanisms involved. Operando shear force modulation spectroscopy is used to observe for the first time the nanoscale dynamics of solid‐electrolyte‐interphase (SEI) formation on the electrode surfaces, confirming that the AZO coating is electrochemically converted into a stiff, homogenous SEI layer that protects the surface from the electrolyte‐induced decomposition. This AZO layer and its resultant artificial SEI‐layer have higher Li‐ion transport rates than the unmodified surface. These layers can reduce barriers to surface nucleation and facilitate rapid redistribution of lithium‐ions during the Li4 Ti5 O12 ⇄ Li7 Ti5 O12 phase separation, significantly inhabiting the orderly collective phase‐separation behavior (electrochemical oscillation) in the LTO electrode. The suppressed voltage oscillations indicate more homogeneous local exchange current density and de/intercalation states with the decorated electrodes, thereby extending their battery efficiency and long‐term cycling stability. This work highlights the ultimate importance of surface treatment for LIB materials for determining their interfacial chemistry and phase transition during the intercalation/deintercalation. Abstract : To study the fundamentals of surface‐decoration effects in a phase‐separation electrochemical system, operando atomic force microscopy spectroscopy is used to observe the dynamics of solid‐electrolyte‐interphase formation on the electrode–electrolyte interfaces of lithium‐titanate‐oxide thin‐film electrodes with/without nanocoating layers; electrochemical measurements confirm that the surface‐decoration can modulate the interface‐reductive‐capability, and improve phase transition kinetics by inhibiting electrochemical oscillations.